Pengembangan Media Audio Visual Ice Breaking (Nyanyian) Wayang Sukuraga Berbasis Nilai Integritas - Oktaviani, Penti; Lyesmaya, Dyah; Sutisnawati, Astri (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
Conditions and atmosphere in the classroom that often seem bored and saturated are a challenge for teachers to break the atmosphere so that learning can take place effectively. Ice breaking is a transition of the situation from boring to excited which can be done by means of games in any form, one of which is singing through audio visuals. This ice breaker model is a method used to break the atmosphere that is not conducive. Ice breaking is also not solely to break the learning atmosphere, but can be done as a delivery of useful meaning or material. One of them is wayang sukuraga which has a variety of good meanings that students need to know to grow their character.  The purpose of this study is to determine and develop audio visual media ice breaking (singing) based on integrity values using the ADDIE Research and Development (R&D) method using data collection in the form of interviews, documentation, and questionnaires. The results of the development of audio-visual media ice breaking (singing) sukuraga puppets based on integrity values are feasible to use in learning with a percentage value from media expert validators of 75.5% with the category "Feasible" and puppet validators of 70% with the category "Feasible".   Keywords: Development; Audio Visual Media; Ice breaking; Wayang Sukuraga; Integrity Values